PENGARUH KETIDAKAMANAN KERJA, KEPUASAN KERJA TERHADAP INTENSI KELUAR KARYAWAN (Studi pada PT “X” di Semarang) - Carina Phrita Lydiasari (Pusbindiklat - LIPI, 2010)
This research is about human resource, especially about turnover intention. This research was done on staf of Spinning PT “X” in Semarang city. The sample obtained 377 samples of staf. The sample selected by randomsampling use stratified random sampling.The analysing use multiple regresion and the hypothesis test use t-test for partial test and F test for Simultaneous test. Mediating analysing use path analysis. The result of the research show that the applicaton of job insecurity and job satisfaction have significant influence on turnover intentions that mediating by commitment organizational of spinning department both of partial and simultaneous.